2009
DOI: 10.3354/meps07811
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of herbivory on kelp by fish and sea urchins differs between inshore and offshore reefs

Abstract: Interactions between water motion, primary productivity, and herbivory are complex. Rates of grazing by fish on tropical coral reefs and by sea urchins on temperate rocky reefs are usually high, but can be low in areas of extreme water motion. Some herbivores can switch between mobile (grazing) and sedentary (drift-feeding) behaviours, and this can be influenced by water motion. We compared the relative consumption of the kelp Ecklonia radiata at rocky reefs in western Australia with different wave exposures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…Dislodgement and erosion were estimated for these nine reefs for each season (autumn, winter, spring 2010, and summer 2011) over 1 yr. In southwestern Australia, grazing by fish and sea urchins is low and little of the biomass produced by kelp is grazed directly, except for some inshore reefs where grazing can be greater (Vanderklift et al 2009). Instead, the majority of the sea urchins in this region (Heliocidaris erythrogramma) feed only on drift material and did not affect the kelp beds (Vanderklift and Wernberg 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dislodgement and erosion were estimated for these nine reefs for each season (autumn, winter, spring 2010, and summer 2011) over 1 yr. In southwestern Australia, grazing by fish and sea urchins is low and little of the biomass produced by kelp is grazed directly, except for some inshore reefs where grazing can be greater (Vanderklift et al 2009). Instead, the majority of the sea urchins in this region (Heliocidaris erythrogramma) feed only on drift material and did not affect the kelp beds (Vanderklift and Wernberg 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The thallus extension was calculated by subtraction of the sum of these two measures by 10 cm. The segment (5 cm) of maximum biomass (for the first 30 cm) was then used to calculate biomass accumulation (BA or kelp productivity, g fresh weight [fresh wt] kelp 21 d 21 ) as BA 5 X fresh wt/5T, where X is the thallus extension (cm), the fresh weight (g) of the heaviest strip, and T is the number of days between punching the holes and collecting the kelp (Vanderklift et al 2009). To convert fresh weight to carbon content, we applied conversion factors of 5.27 fresh weight : dry weight (dry wt; T. Wernberg unpubl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…m -2 ) have previously been recorded in what are considered to be degraded reef ecosystems, especially in sheltered habitats (Bak 1990, Carreiro-Silva & McClanahan 2001. The presence of E. mathaei on wave-washed dynamic reefs has been reported from rocky or temperate environments (Glynn et al 1979, Vanderklift et al 2009) and occasionally from shallow, wave-exposed tropical coral reefs (Russo 1980). It is noteworthy that echinoids on Ningaloo are found in numbers that previously have been recorded primarily from degraded coral reefs.…”
Section: Echinoidsmentioning
confidence: 99%
“…In these highly exposed and wave-swept environments it is essential for the sea urchins to stay within the crevices to avoid being dislodged. Ogden & Lobel (1978) and Vanderklift et al (2009) have shown that under these conditions, sea urchins adopt a sit-and-wait behaviour known as driftfeeding, where individuals feed primarily on food that accumulates in their burrows, only leaving their burrows for very short feeding events within their immediate neighbourhood. Given the high wave activity on Ningaloo, the slope may provide a more energyefficient environment where food availability in relation to energy loss is maximised.…”
Section: Echinoidsmentioning
confidence: 99%